THE DYNAMICS OF SHAHIH AL-BUKHARI COMMENTARIES WITHIN THE OTTOMAN ACADEMIC LIFE - Amiruddin, Muh (RIWAYAH, 2022)
The Ottoman Empire was one of the centers of Islamic power for nearly seven centuries. A very long time in power and covering a vast territory made the Ottoman the center of Islamic civilization for a very long time. The education, culture, and civilization of the Ottoman were built on the madrasa system established from the time of the Seljuks and the scientific knowledge that was widespread in Anatolia through the madrasas. This madrasa system had previously been found in Egypt and Damascus. The development of education is also related to the development of hadith studies in the Ottoman, especially the study of Sahih al-Bukhari. This study aims to determine the development of the study of Sahih al-Bukhari in the Ottoman period. This study using literary research showed that the first Commentary written on Sahih al-Bukhari in the Ottoman was a work called al-Kawsar al-Jari written by Molla Gurani in the fifteenth century. In addition, a total of six commentaries were written, one in the late fifteenth century and the other in the sixteenth century. In the seventeenth century, many hadith scholars from Islamic scientific centers began to come to Istanbul, especially after Egypt entered the rule of the Ottoman Turks. In the eighteenth and nineteenth centuries, seven studies were carried out on Sahih al-Bukhari. Especially the study of special qualities in the nineteenth century which is pleasing in terms of the science of hadith. The most important indicator is the study of the methodology and commentary of hadith which appears together with the educational activities of scholars who have a high level of accumulation of hadith.[Dinamika Pensyarahan Shahih al-Bukhari dalam Dunia Akademik Turki Usmani. Turki Usmani adalah salah satu pusat kekuasan Islam selama hampir tujuh abad. Waktu berkuasa yang sangat lama dan meliputi cakupan wilayah kekuasaan yang luas membuat Turki Usmani menjadi pusat peradaban Islam dalam masa yang sangat lama. Pendidikan, budaya, dan peradaban Utsmaniyah dibangun di atas sistem madrasah yang didirikan oleh Seljuk dan pengetahuan ilmiah yang tersebar luas di Anatolia melalui madrasah. Sistem madrasah ini sebelumnya telah banyak ditemukan di Mesir dan Damaskus. Perkembangan pendidikan tersebut juga berkaitan dengan perkembangan studi hadis di Turki Usmani, khususnya studi atas Shahih al-Bukhari. Penelitian ini bertujuan untuk mengetahui perkembangan studi terhadap Shahih al-Bukhari di Turki Usmani. Studi dengan metode kepustakaan ini menunjukkan bahwa komentar pertama yang ditulis tentang Shahih al-Bukhari di Ottoman adalah karya bernama al-Kawsar al-Jari yang ditulis oleh Molla Gurani pada abad kelima belas. Selain itu, sebanyak enam komentar telah ditulis, satu pada akhir abad kelima belas dan yang lainnya pada abad keenam belas. Pada abad ketujuh belas, banyak ulama hadis dari pusat-pusat keilmuan Islam mulai berdatangan ke Istanbul, terutama setelah Mesir masuk dalam kekuasaan Turki Usmani.  Pada abad kedelapan belas dan kesembilan belas, tujuh studi dilakukan pada Shahih al-Bukhari. Khususnya studi kualitas khusus pada abad kesembilan belas yang menyenangkan dalam hal ilmu hadits. Indikator terpentingnya adalah kajian metodologi dan syarah hadis  yang muncul bersamaan dengan aktivitas pendidikan ulama yang memiliki tingkat akumulasi hadis yang tinggi.]